Rural Women and Information on Natural Resources: Rural Women in Aceh’s Struggle for Agency - Abdullah Abdul Muthaleb (Jurnal Perempuan, 2019)
Rural women have the potential to mobilize herself and her community towards a sovereign and just rural community. However, rural women frequently face form of discrimination that impede them to achieve their maximum potential. In the midst of forest and land degradation, those gender-based discrimination also prevent women from participating in land and forest governance that is vital for the rural community’s livelihood. An example of form of gender-based discrimination experienced by women in several regions in Aceh is discrimination in accessing public information. This article describes and analyses several Aceh women’s experiences in using the rights-based approach on access to information. The women in this article have used the Law on Public Information as the basis for their advocacy towards the land and forest governance in their residential area. These experiences of the rural women have shown shows that women have not only interests upon the information on natural resources, but they also possess capability, perseverance, and will to obtain such information.